1999
DOI: 10.1042/cs0970079
|View full text |Cite
|
Sign up to set email alerts
|

Changes in muscle strength in women following the menopause: a longitudinal assessment of the efficacy of hormone replacement therapy

Abstract: The effects of hormone deficiency at the menopause on muscle strength was examined in 10 healthy middle-aged women (1-3 years post-menopause) in a longitudinal trial over 39 weeks. Performance was compared with that of age-matched females (n=11) taking a course of hormone replacement therapy (HRT). Muscle strength of the quadriceps was measured isometrically at 90 degrees of knee flexion and at angular velocities of 1.05, 2.09 and 3.13 rad/s using an isokinetic dynamometer. Hand grip strength was assessed by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 30 publications
0
44
0
3
Order By: Relevance
“…Hormonal replacement therapy (HRT) has been shown to promote the maintenance or increase total fat-free mass (FFM) (Haarbo et al, 1991;Greeves et al, 1999;Skelton et al, 1999). As such, estrogens may have a direct effect on muscle via its estrogen receptors (Lemoine et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal replacement therapy (HRT) has been shown to promote the maintenance or increase total fat-free mass (FFM) (Haarbo et al, 1991;Greeves et al, 1999;Skelton et al, 1999). As such, estrogens may have a direct effect on muscle via its estrogen receptors (Lemoine et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that hormone replacement therapy (HRT) prevents the shift in body fat distribution to a more central location (5)(6)(7) and diminishes the loss of muscle strength (8)(9)(10)(11)(12)(13)(14)(15). Unfortunately, HRT use is accompanied by adverse side effects, such as an increased risk of breast cancer and cardiovascular disease (16), and for this reason its long-term use is not advocated.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the trials focused on small muscle groups. The two latest studies reported a protective 13 and an increasing effect on muscle strength 14 supporting the applicability of hormone replacement therapy to preserve muscle strength. Our results confirm the positive outcome of Skelton's study 14 , in which conjugated oestrogens in combination with medroxyprogesterone acetate were used.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for this discrepancy might be the large variations in study design and study drug used 12 . The two most recent studies report a protective effect of hormone replacement therapy on loss of muscle strength 13 and a strength-increasing effect 14 .…”
Section: Introductionmentioning
confidence: 99%